Renal function in patients with chronic hepatitis B during antiviral therapy - Nerma Čustović; Lejla Alić; Ismar Rašić; Aida Saray; Amila Mehmedović; Nadža Zubčević (Medicinski glasnik, 2023)
Aim: To analyse the impact of the length of antiviral therapy with tenofovir disoproxil fumarate (TDF) on the renal function in patients with chronic hepatitis B (CHB). Methods: A cross-sectional study included 75 patients with CHB treated with tenofovir, who had a normal renal function at the beginning of the treatment. Renal function was determined based on glomerular filtration rate (eGFR) value using the Modification of Diet in Renal Disease formula (MDRD). Measurement of serum creatinine concentration and urinary protein excretion were performed using standard laboratory analyses. Viral load quantification (HBV-DNA) was determined by polymerase chain reaction (PCR). The degree of liver fibrosis was determined using fibrosis4 (FIB-4) and aspartate transaminase to platelet ratio index (APRI) fibrosis score. Results: Out of 75 CHB patients, 37 were on antiviral treatment for up to 2 years (group 1) and 38 patients on antiviral treatment longer than two years (group 2). Mean age of patients was not significantly different between the groups (p=0.076), nor was the gender distribution. There was no statistically significant difference between the mean values of the eGFR in the two groups (91.89±9.24 vs. 88.42±7.84 mL/min/1.73m2 ; p=0.42), as well as between the mean values of serum creatinine (p=0.360) and 24-hour urine protein excretion (p=0.380). There was no statistically significant correlation between renal parameters and viral load, APRI and FIB-4 fibrosis score. Conclusion: Results: of our study did not show significant changes in the measured parameters of renal function in group 1 and group 2 of patients, regardless of the length of antiviral treatment, indicating a good renal safety profile of TDF.
Keywords: kidney; liver; tenofovir